THE EFFECT OF PRICE, PRODUCT QUALITY, AND ELECTRONIC WORD OF MOUTH (EWOM) ON THE INTENTION TO BUY SUNRIZQ BATIK IN MALAKA MALAYSIA - Abd Rofiq; Joko Suyono (Journal of World Conference (JWC), 2019)
Buying interest is the desire that arises from consumers to a product as a result of the consumer's observation of a product. Therefore the purpose of this study is to analyze the extent of the influence of Price, Product Quality, Electronic Word Of Mouth (EWOM) on consumer buying interest. Batik Sunrizq Malacca Malaysia. This research is quantitative research with a sample of 240 respondents. Furthermore, the data were analyzed using multiple linear regression analysis techniques and classical assumption tests. The results of this study indicate that the three hypotheses proposed have a significant and supportive effect